2007
DOI: 10.1158/1078-0432.ccr-06-2450
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Distribution and Adhesion Receptor Expression in Metastatic Melanoma

Abstract: Purpose: Metastatic malignant melanoma is a devastating disease with a poor prognosis. Recent therapeutic trials have focused on immunotherapy to induce development of endogenous antitumor immune responses. To date, such protocols have shown success in activation of tumor-specific CTL but no overall improvement in survival. To kill tumor, antigen-specific CTL must efficiently target and enter tumor tissue.The purpose of this study was to examine the pathway of leukocyte migration to metastatic melanoma. Experi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 56 publications
3
54
1
2
Order By: Relevance
“…Moreover, intratumoral vessels in murine tumor models (e.g., RIP-Tag5 pancreatic tumors, EMT6 mammary tumors, CT26 colon tumors, B16 melanoma) poorly express primary adhesion molecules (e.g., E-selectin), chemokines (e.g., CXCL9, CXCL10) or prototypical arrest molecules such as intercellular adhesion molecule-1 (ICAM-1) or vascular adhesion molecule-1 (VCAM-1) [23,25,26,[42][43][44][45][46][47][48]. These observations in murine tumors correspond with histologic studies showing limited expression of adhesion molecules and chemokines in the intratumoral region of human tumors [23,25,26,42,45,[49][50][51].…”
Section: Limited Leukocyte Interactions With Tumor Vessels Under Steamentioning
confidence: 58%
“…Moreover, intratumoral vessels in murine tumor models (e.g., RIP-Tag5 pancreatic tumors, EMT6 mammary tumors, CT26 colon tumors, B16 melanoma) poorly express primary adhesion molecules (e.g., E-selectin), chemokines (e.g., CXCL9, CXCL10) or prototypical arrest molecules such as intercellular adhesion molecule-1 (ICAM-1) or vascular adhesion molecule-1 (VCAM-1) [23,25,26,[42][43][44][45][46][47][48]. These observations in murine tumors correspond with histologic studies showing limited expression of adhesion molecules and chemokines in the intratumoral region of human tumors [23,25,26,42,45,[49][50][51].…”
Section: Limited Leukocyte Interactions With Tumor Vessels Under Steamentioning
confidence: 58%
“…We further determined that the moderate intravascular density of ICAM-1 detected on tumor vessels was not sufficient to support efficient extravasation of CD8 + Teffs. These findings provide a functional explanation for the modest steadystate level of infiltration observed for endogenous or adoptively transferred CD8 + T cells in murine tumors (B16, RIP-Tag5) (27,28,36,38) or patient tumors (metastatic melanoma, squamous cell skin carcinoma) (39,40) in regions where vessels were weakly immunostained for E-selectin, ICAM-1, or VCAM-1. When the function of tumor-reactive T cells was monitored after bolus infusion under conditions commonly used in preclinical and clinical protocols to boost circulating Teff populations (3), we found that basal trafficking of CD8 + Teffs across tumor vessels was insufficient to mediate apoptosis of tumor targets.…”
Section: Discussionmentioning
confidence: 73%
“…However, this inflammatory environment appears to fail to induce the expression of vascular adhesion molecules on intratumoral vessels. This has been demonstrated in experimental models of melanoma and carcinoma (81), as well as in human cutaneous squamous cell carcinoma, Merkel cell carcinoma, and metastatic melanoma tissue (74, 75, 82). This lack of responsiveness to inflammatory signals has been termed endothelial anergy (83) and may play an important role in the exclusion of antitumor immune effector cells from the tumor microenvironment.…”
Section: Role Of the Tumor Vasculature In Immune Cell Exclusionmentioning
confidence: 84%